Re_ThiNk Precacore. Ideas for the Future for the Ancient Village. Projects and Processes for Innovating and Enhancing - Natalina Carrà (ArcHistoR Architettura Storia Restauro: Architecture History Restoration, 2020)
Villages are living books in which civilizations have written their history. They are the product of community identities and, at the same time, they are “generators of belonging”. The ancient village of Precacore is located in the Park of the Aspromonte, and the particular combination of nature and human work makes this place unique. This advantageous condition is at the base of possible design opportunities. A situation that can become a source of great interest for potential design opportunities based on the main idea that Precacore could become an essential element for the construction of the cultural identity of the Park. In the processes of construction and promotion of the image of the territory of the Park the ancient village could become a strategic resource if proper strategies and policies are pursued. Among the purposes, for example, the idea to enhance talented and creative skills should be promoted, and to invent places of interaction encouraging relationships and innovation as well. The final purpose is to promote a positive perception of the site (the village and the Park) at local, national and international level, and to provide innovative services and functions to attract people and resources useful for the promotion of local development.